Developing a modern radiotherapy department in a rural hospital in Cameroon: The Mbingo experience - Ntumsi Akundoh Tontu; William W.Y. Cheung; Marcus Jones; Linda Grossheim; Dennis Palmer; Earnest Chukwudi N. Okonkwo; Eric Moore; Keith Streatfield; Laurie Elit (Technical Innovations & Patient Support in Radiation Oncology)
Although radiotherapy is critical for cancer cure and palliation, access to such expensive and sophisticated technology is very limited in low- and middle-income countries (LMIC). Cancer incidence in Africa is currently 1.5 million case per year, thus urgent and innovative solutions are required to build necessary infrastructure needed to address this global health challenge. We describe our approach and challenges as a faith based non-government organization in setting up a modern radiotherapy department in a rural hospital in Cameroon to mitigate this unmet need. We highlite our engagement with international bodies and individuals for fund raising and volunteerism, local radiotherapy workforce development and training (radiation oncology, dosimetrists, radiation therapist and medical physicists) and the expertise required for construction of the bunker and installation of the Linac machine.